"The pen is mightier than the sword": Linking educational history and accounting history in shaping historical thought. (February 2015) - Black, John
Traditionally it has been assumed that the rank and file of the British Army of the eighteenth and nineteenth centuries were illiterate and innumerate and the government of the day had no desire to educate the lower ranks. However this may not be an accurate portrayal. This article demonstrates that there were always enough rank-and-file soldiers who could read, write and keep simple accounts – and thereby perform routine bookkeeping and clerical duties – within any British Army regiment or formation of the day. Clerical administrative and pay duties increased after the reforms of the Army, first in 1782 and later in 1797. However, until 1812 the Army was not officially concerned with providing elementary education to the common soldier. The Army administraetive and financial reforms of the late eighteenth century predated the existence of professional accounting bodies or official forms of state elementary education. However, these reforms made the Army more accountable to Parliament in terms of the size of the Army and its finances, and the existence of soldiers in the ranks that possessed the necessary basic education to undertake the increasing number of routine clerical duties enabled the success of these reforms.